From political to social generations: a critical reappraisal of Mannheim’s classical approach - Aboim, Sofia; Vasconcelos, Pedro (European Journal of Social Theory, 2014)
Faced with the confused meanings of the concept of generation, this article defends the need to move from Karl Mannheim’s excessive emphasis on political and intellectual self-awareness as a pre-condition for generation formation to an enlarged social and cultural definition of generations. By developing the concept of social generations, we argue that rather than concrete groups, generations are better conceived as discourses with which individuals relate in order to build self-identification. Individuals living in similar historical contexts may share mental and practical dispositions, but must always position themselves in face of the narratives that have come to be dominant to describe a given generational location. Such a contention implies redressing Mannheim’s culturalist view through a reformulation of his hierarchical view of the scheme of generations. By replacing generation-units by dominant ideas, we contend that generations are better conceived as discursive formations in the Foucauldian sense.